Associations between weight status, body satisfaction, ethnic identity and self‐esteem in Oceanian adolescents. Issue 12 (29th June 2021) - Frayon, Stéphane; Swami, Viren; Wattelez, Guillaume; Todd, Jennifer; Galy, Olivier
Summary: Background: Self‐esteem has consistently been observed to be relatively low in adolescents with obesity. In the Pacific region, the prevalence of obesity in adolescence is high, but few studies have considered issues of self‐esteem in this population. Objective: To examine associations between weight status, body dissatisfaction and self‐esteem in a sample of New Caledonian adolescents and to test for moderation effects of ethnicity on predictors of self‐esteem. Methods: Objective anthropometric measures (height, weight, waist circumference and thickness of skinfolds) were obtained in a multi‐ethnic sample of New Caledonian adolescents. Body mass index (BMI), waist‐to‐height ratio and the sum of four skinfolds thickness were used as proxies of weight status. Indices of ethnic identity, self‐esteem, socio‐demographic data (socioeconomic status, ethnicity, gender, urbanicity of residence) and body dissatisfaction were obtained using survey methods. Results: Between‐group analyses indicated that adolescents of European/white origin had significantly higher self‐esteem than adolescents with Oceanian Non‐European Non‐Asian ancestry (ONENA). However, low self‐esteem was significantly associated with weight status and body dissatisfactions in European/white adolescents but not ONENA adolescents. Ethnicity moderated the relationships of predictors (BMI z ‐score, body dissatisfaction, age, urbanicity and ethnic identity) on self‐esteem, and the strongest predictors of self‐esteem were ethnicity and ethnic identity. Conclusions: While self‐esteem has important consequences for adolescent well‐being and health outcomes, these results highlight the importance of applying different steps to develop and maintain healthy self‐esteem in the Pacific region.